Jujur Sebagai Landasan Utama Konseling Islam dalam Perspektif Hadist - Albaar, Ragwan; Basyid, Abd; Silawarti, Amelia Ismah; Ulfah, Fania; Islamiyah , Nadhifatul Ilmi (Jurnal Bimbingan dan Konseling Islam, 2024)
This research aims to deepen the concept of honesty as the main foundation of Islamic counseling based on the Hadith narrated in Sunan Darimi, index number 2599. The Hadith narrated in Sunan Darimi, index number 2599, was chosen as the focus of this research because it contains elements related to honesty. This research uses qualitative research methods involving in-depth analysis of hadiths with a literature study approach and contextual understanding. The literature review focuses on the Sunan Darimi book and related literature from Google Scholar and Scopus. The research results indicate that honesty is not only an important value in daily life but also a fundamental basis in Islamic counseling that can build trust and enhance the effectiveness of counseling. These findings provide a solid foundation for Islamic counselors to conduct counseling practices with strong ethics, create an open environment, and integrate Islamic values in guiding individuals towards spiritual and psychological well-being. An honest counselor reflects Islamic integrity, in accordance with Hadith teachings that emphasize honesty as an important foundation.